Implementasi Model Pembelajaran Berbasis Masalah Berbantuan Media Gambar Seri dalam Pembelajaran Menulis Cerita Sederhana pada Siswa Kelas II Sekolah Dasar - Hidayati, Fatmi Rohmah Nur; markhamah, markhamah; rahmawati, fitri puji; rahmawati, laili etika (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
Numerous difficulties with learning technique, particularly with regard to learning methodologies, exist in the reality of education. The purpose of this study is to elucidate how advanced writing materials for class II elementary school pupils use Problem Based Learning (PBL). Reading, writing, speaking, and listening are the four language abilities that are relevant to learning Indonesian. Writing is regarded as the most difficult of these four subjects for primary school pupils in lower grades. The SDIT Muhammadiyah Al Kautsar teachers and class II students were the study's resource people and data sources. The Miles and Huberman technique was used to examine the data, which was obtained through observation, interviews, and documentation. The findings indicate that PBL learning, coupled with serial image media, proves effective in enhancing students' advanced writing abilities. Consequently, it is inferred that PBL learning, complemented by serial image media, encourages greater student engagement by facilitating the expression of their ideas, opinions, and imaginative storytelling. The serial image media aids students in locating vocabulary and presenting the contents of images in a systematic narrative. GThe application of Problem Based Learning with Ganbar Series Media in the second-grade class reveals that, out of 30 students, five exhibit deficiencies in vocabulary and struggle with organizing the story sequence. 9 Students who write stories with a vocabulary of 40-50 vocabulary words, with the appropriate story order. And there were 16 students who were able to write stories with a vocabulary of more than 50 words with a good and systematic story sequence.